Methodology for measuring the gap size using a fiber-optic displacement sensor exemplified by a centrifugal blood pump - Gawlikowski, Maciej; Kurtyka, Przemysław; Zalewski, Jerzy; Zarwańska-Doffek, Magda; Kapis, Artur (Photonics Letters of Poland, 2020)
In order to avoid blood clotting, in the second generation of rotary blood pumps the impeller is suspended without mechanical bearing, using balance of magnetic and hydrodynamic forces. Reaching single tens of microns gap between pump housing and impeller is crucial for level of blood traumatization by the pump. In this paper we would like to present the method of physical measurement of this gap on a running pump with the use of commercial fiber-optic proximity sensor on the example of Polish rotary blood pump ReligaHeart ROT. We also discussed technical requirements of the construction of laboratory stand. Full Text: PDF References S. Westaby, "Rotary blood pumps as definitive treatment for severe heart failure", Future Cardiol. 9, 2 (2013). CrossRef R. Delgado, M. Bergheim, "HeartMate® II left ventricular assist device: a new device for advanced heart failure", Epert Rev. Med. Devices, 2, 5 (2005). CrossRef M. Ozban, T. Yagdi, C. Engin et al, Transplant proc., 44, 6 (2012). CrossRef A.T. Lanfear, M. Hamandi, J. Fan et al., "Trends in HeartMate 3: What we know so far", J. Card. Surg., 35, 1 (2020). CrossRef Ch. Zengsheng, S. Anqiang, W. Hongyu, "Non-physiological shear stress-induced blood damage in ventricular assist device", Medicine in Novel Technology and Devices, 3 (2019). CrossRef A. M. Robertson, A. Sequeira, R. G. Owens, Rheological models of blood In: L. Formaggia, A. Quarteroni, A Veneziani (eds) Cardiovascular Mathematics (Milano, Springer-Verlag 2009) CrossRef M. Gawlikowski et al., "Necessity of telemonitoring in patients treated by means of cardiac assist systems on the example of Polish rotary blood pump ReligaHeart ROT", Advances in Intelligent Systems and Computing, 925 (2019). CrossRef R. Kustosz, et al., "The tin coating utilisation as blood contact surface modification in implantable rotary left ventricle assist device religaheart ROT", Arch. Matall. Mater., 60, 3 (2015). CrossRef S. S. Patil, A. D. Shaligram, "Analytical study of performance variations of fiber optic micro-displacement sensor configurations using mathematical modeling and an experimental test jig", IJSER, 4, 11 (2013). DirectLink Philtec Application Note, 6, 25 (2017) CrossRef